THE RELATIONSHIP BETWEEN DRIVING DURATION AND THE INCIDENCE OF MYOFASCIAL PAIN SYNDROME IN THE UPPER TRAPEZIUS MUSCLE IN MICROBUS DRIVERS AT UBUNG TERMINAL - Yudi Pramana Putra; Ni Luh Putu Gita Karunia Saraswati; Sayu Aryantari Putri Thanaya (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2021)
ABSTRACT Myofascial pain syndrome is commonly felt by drivers who perform activities in a static and repetitive manner for long durations. Myofascial pain syndrome is caused by a change in cervical posture, leading to excessive burden and tightness in the upper trapezius muscle. Complaints are described as pain due to the suppression of nociceptor nerve fibers in the neck and shoulder area. The objective of this study was to determine the relationship between driving duration and the incidence of myofascial pain syndrome in the upper trapezius muscle in microbus drivers at Ubung Terminal, specifically drivers majoring the Singaraja-Denpasar/Denpasar-Singaraja route. The sampling technique used in this study was consecutive sampling. This study used an observational method with a cross-sectional design. Data were collected from 64 microbus drivers majoring the Singaraja-Denpasar/Denpasar-Singaraja route at Ubung terminal. The results showed a significant relationship between driving duration and myofascial pain syndrome with a correlation of 0.426 and a p-value of 0.000 (p <0.05). It can be concluded that there is a relationship between driving duration and the incidence of myofascial pain syndrome in the upper trapezius muscle in microbus drivers at Ubung Terminal. In the future, follow-up research can be conducted to see the long-term effects of changes in posture and driving duration, and the sample size can be increased by taking the entire population of terminals in Bali. Keywords: Myofascial pain syndrome, driving duration, visual analogue scale